The congress of religion - Melton, George Lane (My University, 1893)
Introduction: A great many of us are doubtless looking forward to our visit to the Worlds Fair as one of the great events of our lives. There will probably be another such chance to see and hear what will be crowded into the small amount of space and time, at least for us, in our life time.
Citation: Melton, George Lane. The congress of religion. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Worlds fair; Religion; Congress; Theses; Manuscripts (documents)